Can Essential Oils/Botanical Agents Smart-Nanoformulations Be the Winning Cards against Psoriasis? - Mohamed Ashraf; Hossam S. El-Sawy; Ghada M. El Zaafarany; Mona M. A. Abdel-Mottaleb (MDPI AG, 2023)
Although psoriasis remains one of the most devastating inflammatory disorders due to its huge negative impact on patients' quality of life, new "green" treatment approaches still need to be fully explored. The purpose of this review article is to focus on the utilization of different essential oils and active constituents of herbal botanical origin for the treatment of psoriasis that proved efficacious via both in vitro and in vivo models. The applications of nanotechnology-based formulations which displayed great potential in augmenting the permeation and delivery of these agents is also addressed. Numerous studies have been found which assessed the potential activity of natural botanical agents to overcome psoriasis. Nano-architecture delivery is applied in order to maximize the benefits of their activity, improve properties, and increase patient compliance. This field of natural innovative formulations can be a promising tool to optimize remediation of psoriasis while minimizing adverse effects.